Empowering Community for Liquid Compost Production from Household Waste at the “Restu Ibu” Waste Bank in Yogyakarta, Indonesia - Gita Indah Budiarti; Siti Salamah; Endah Sulistiawati; Rachma Tia Evitasari (Indonesia Berdaya, 2026)
Community-based waste banks play a crucial role in promoting sustainable waste management and local economic empowerment. The “Restu Ibu” waste bank in Sambilegi, Sleman Regency, faces challenges related to limited product innovation, human resource capacity, and economic aspects, particularly product pricing and commercialization. This community engagement program aimed to enhance the technical skills and pricing determination capabilities of female waste bank members through applied chemical innovation and economic capacity building. The program employed offline counseling and hands-on training focused on producing liquid compost fertilizer from household organic waste using simple batch reactors made from locally available materials. Program effectiveness was evaluated through post-test assessments, participant interaction, interviews, and reviews of financial records. The results showed a 100% increase in participants’ knowledge of liquid compost production and reactor concepts, with comprehension levels improving from low (scores 1–2) to high (scores 3–4) among 88% of participants. Active engagement during training further indicated effective knowledge transfer. Overall, the program strengthened individual and institutional capacity, supported sustainable organic waste valorization, and enhanced the potential of the waste bank to contribute to local economic development and tourism-oriented community initiatives.